Rapid campimetry - a novel robust kinetic approach for visual field screening in glaucoma - Al-Nosairy, Khaldoon O.; Rodenbeck, Katharina; Vorholt, Sophie; Djouoma, Nidele; Thieme, Hagen; Müller, Fabian; Hoffmann, Michael B. (Frontiers in Medicine, 2024)
Purpose To investigate the robustness and variability of a novel kinetic visual field (VF) screening method termed rapid campimetry (RC). Methods In RC visual field (VF) screening is enabled via kinetic-based testing on any computer (10°/4.7 s at 40-cm viewing distance) and high contrast in a dark room (1 cd/cm2). In experiment (1): 30 participants [20 healthy participants (HC), 5 glaucoma patients (GLA) and 5 patients with cataract (CAT)] were included to test the intra-session variability (fatigue effect) and the following effects on RC: room illumination (140 cd/m2), ±3 D refractive errors, media opacity. In experiment (2): Inter-session variability (1–3 weeks apart) was assessed in 10 HC and 10 GLA. Since RC detects absolute scotomas, the outcome measure was the size of physiological (blindspot) and pathological (glaucoma) scotomas in degrees. A repeated measures ANOVA was employed in experiment 1 and intraclass correlation (ICC) in experiment 2. Results Neither the size of the blindspot nor the VF defects differed significantly between the different testing conditions. For intra-session variability, the average bias of blindspot size was −0.6 ± 2.5°, limits of agreement (LOA), in comparison to 0.3 ± 1.5° for VF defects, both with ICC of 0.86 and 0.93, respectively. For the inter-session repeatability, the average bias and LOA for blindspot size was 0.2 ± 3.85° in comparison 1.6 ± 3.1° for VF defects, both with ICC of 0.87 and 0.91, respectively. Conclusion RC was robust to suboptimal testing VF conditions and showed good-to-excellent reliability between VF testing visits holding high potential for teleophthalmology.